2022
DOI: 10.1007/s11142-022-09689-x
|View full text |Cite
|
Sign up to set email alerts
|

Audit process, private information, and insider trading

Abstract: While the shareholder benefits of audits are well documented, evidence on whether audits can facilitate opportunistic behavior by corporate insiders is scarce. In this paper, we examine whether the audit process facilitates one particular form of opportunism: informed trading by corporate insiders. We focus our analysis on insider trading around the audit report date. We find an increase in trading around the audit report date and that the increase is abnormally large for firms that subsequently report modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 45 publications
3
5
0
Order By: Relevance
“…Additionally, Beneish and Vargus (2002) provided evidence that one year ahead of income, accruals are significantly lower when accompanied by abnormal insider selling and greater when accompanied by abnormal insider buying. Hallman et al (2020) and Arif et al (2022) investigated the association between insider trading and audit opinions. In particular, Hallman et al (2020) found that insider sales increased two to four years before the issuance of audit going-concern opinions but dropped significantly in the year of such opinion due to the early communication between auditors and their most important clients (i.e.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Beneish and Vargus (2002) provided evidence that one year ahead of income, accruals are significantly lower when accompanied by abnormal insider selling and greater when accompanied by abnormal insider buying. Hallman et al (2020) and Arif et al (2022) investigated the association between insider trading and audit opinions. In particular, Hallman et al (2020) found that insider sales increased two to four years before the issuance of audit going-concern opinions but dropped significantly in the year of such opinion due to the early communication between auditors and their most important clients (i.e.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…insiders’ firms) regarding their audit opinions. Similarly, Arif et al (2022) identified that the size of insider trading surges around the audit report date, and such an increase is greater for firms that will receive modified opinions. As a result, insider trading is encouraged when firms anticipate possible modified auditor opinions.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We share Arif et al ’s (2022) view that, during their audit engagement, auditors produce and accumulate private information concerning their clients. In this paper, we argue that audit adjustments represent one element of such private information pertinent to audit risk, especially, the persistence aspect of it.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
“…We share Arif et al's (2022) view that, during their audit engagement, auditors produce and accumulate private information concerning their clients. In this paper, we argue that audit…”
Section: Audit Adjustment Mechanism and Audit Pricingmentioning
confidence: 99%